Immunity, Sex and Parasites: Does Sex of Sand-Field Cricket (Gryllus firmus) Affect Immune Response to Eugregarine Parasites? - Shaw, Ashley (MacEwan University Student eJournal, 2016)
There is controversy about the effects gut-dwelling eugregarine parasites have on their invertebrate hosts. If crickets (Gryllus firmus) apportion resources to reproduction differently in males vs. females, then resources used to mount immune responses to parasites may also differ – especially if the parasites are pathogenic. I investigated the possible differences in immune response between male and female crickets and attempted to determine whether these differences are related to intensity of parasitic infection. To do this, pieces of nylon filament were implanted into the hemocoel of crickets which tested the immune response where hemocytes surround the filament (encapsulation). These responses were compared to intensity of parasitic infection. No statistically significant relationship between sex and melanisation, or sex and parasite load were found. I found that the duration of melanization was negatively correlated to parasite abundance and that there was a positive correlation between body size and parasite number. This result suggests the existence of a relationship between the parasite and host that could be conflicting with sexual selection theory, such as host manipulation by the parasite.